1997
DOI: 10.1007/bf02786394
|View full text |Cite
|
Sign up to set email alerts
|

Selection of the MHC Class II-associated peptide repertoire by HLA-DM

Abstract: During the past five years considerable progress has been made in the field of major histocompatibility complex (MHC) class II-restricted antigen presentation. Several observations made in mutant cell lines with a presentation defect led to the identification of a novel protein, the nonclassic MHC class II molecule human leukocyte antigen (HLA)-DM. Cell biological and biochemical characterization of HLA-DM provided deeper insight into the molecular mechanism underlying the loading process: HLA-DM accumulates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Introduction of functional tapasin into these cells restores normal class I expression and functional Ag presentation (7,9,(13)(14)(15)(16). These multiple functions of tapasin have led to speculation that it may be involved in peptide editing of class I bound ligands (10, 16 -21) in a manner similar to that of HLA-DM in class II Ag presentation (22). More recent studies have provided biochemical evidence for a specific peptide-editing function for tapasin (9).…”
mentioning
confidence: 99%
“…Introduction of functional tapasin into these cells restores normal class I expression and functional Ag presentation (7,9,(13)(14)(15)(16). These multiple functions of tapasin have led to speculation that it may be involved in peptide editing of class I bound ligands (10, 16 -21) in a manner similar to that of HLA-DM in class II Ag presentation (22). More recent studies have provided biochemical evidence for a specific peptide-editing function for tapasin (9).…”
mentioning
confidence: 99%
“…Strikingly, these experiments revealed that mice lacking DM expression generated greatly enhanced responses to the HEL 103-117 I-E restricted epitope compared with WT mice (Fig. 6B), despite eliciting similarly low responses to the I-A d restricted HEL (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) peptide. These results suggest that the preimmune T cell repertoire in DM Ϫ/Ϫ mice is enriched for I-E restricted CD4 T cells.…”
Section: Dm-dependent I-e-restricted Peptides Recruit More T Cells Inmentioning
confidence: 92%
“…To accurately assess the immunodominance pattern to the MalE Ag, we established arbitrary exclusion criteria, with responses consistently representing 4% or less of the total response being eliminated from further analysis. Using this criterion, we found that CD4 T cells from WT mice responded to a total of 9 peptide pools (pools 8,11,12,14,15,16,21,26, and 30), including 8, 11, and 26, pools that contain peptides corresponding to previously characterized MalE epitopes (45,46). Interestingly, when responses in DM Ϫ/Ϫ mice were analyzed, a similar number of peptide pools elicited a productive IL-2 response, with a total of 8 (pools 4,7,8,10,11,12,14, and 16) displaying reactivity above 4% of the total response.…”
Section: Identification Of the Immunodominance Pattern To Male Ag Inmentioning
confidence: 99%
See 1 more Smart Citation
“…li generates CLIP, subsequently released from the MHC class IIbinding grove in a peptide editing process catalyzed by the nonclassical MHC class II molecules HLA-DMA/DMB. 8 HLA-DM acts as a chaperone and protects empty MHC class II complexes until they are able to bind peptides that show sufficient stability to bind to MHC class II molecules. Despite the fact that MHC class II molecules, Ii and HLA-DM are encoded on separated chromosomes, they are partially coregulated by the class II transcriptional activator CIITA.…”
mentioning
confidence: 99%